Macroeconomics determinants of sovereign credit ratings - Soh, Wei Chee; Cheng, Fan Fah; Md. Nassir, Annuar (Canadian Center of Science and Education, 2015)
The objective of this paper is to identify the determinants of sovereign credit rating. This study including 53 countries in the study covers from year 2000 to 2011. This study examines nine macroeconomic variables and extended by using three qualitative variables, i.e., history of default, economic development and economic freedom. The results are consistent with previous studies that some macroeconomics variables are determinants of rating. Furthermore, the economic freedom variable serves as a vital factor in determining sovereign credit rating that has been overlooked by the previous studies. This study has added new findings and indicates that the economic freedom of country is decisive factor in assessment.